Differentiation of workers into soldiers is associated with a size reduction of higher-order brain centers in the neotropical termite Procornitermes araujoi - Valadares, Lohan; da Silva, Iago Bueno [UNESP]; Costa-Leonardo, Ana Maria [UNESP]; Sandoz, Jean-Christophe (Springer Nature, 2023)
Comparing the size of functionally distinct brain regions across individuals with remarkable differences in sensory processing and cognitive demands provides important insights into the selective forces shaping animal nervous systems. We took advantage of the complex system of worker-to-soldier differentiation in the termitid Procornitermes araujoi, to investigate how a profound modification of body morphology followed by an irreversible shift in task performance are translated in terms of brain structure and size. This behavioural shift is characterised by a reduction of the once wide and complex behavioural repertoire of workers to one exclusively dedicated to nest defence (soldiers). In accordance with soldier’s reduced cognitive and sensory demands, we show here that differentiation of workers into soldiers is associated with a size reduction of the mushroom body (MB) compartments, higher-order brain regions responsible for multimodal processing and integration of sensory information, as well as learning, memory, and decision-making. Moreover, in soldiers, we found an apparent fusion of the medial and lateral MB calyces likely associated with its volume reduction. These results illustrate a functional neuroplasticity of the MB associated with division of labour, supporting the link between MB size and behavioural flexibility in social insect workers.